Red planet [videorecording (DVD)] - Kilmer, Val, 1959-; Sizemore, Tom, 1961-; Moss, Carrie-Anne, 1970-; Revell, Graeme (Warner Home Video, 2001)
In the mid-21st century, the nations of a dying Earth look starward for a solution and set out to colonize Mars. But something no one could have expected awaits. Houston, we have big trouble.